Not a bathtub: A consideration of sea-level physics for archaeological models of human migration. (January 2022) - Borreggine, Marisa; Powell, Evelyn; Pico, Tamara; Mitrovica, Jerry X.; Meadow, Richard; Tryon, Christian
Abstract: Accurately reconstructing past sea level is key to simulating potential migration pathways of ancient hominins, including early Homo sapiens . Models of ancient human migration events commonly construct estimates of paleoenvironments using the "bathtub" model, in which sea level is assumed to rise and fall according to a "eustatic" (global average) value over time. However, large uncertainties exist on past ice sheet sizes and shapes, particularly prior to the Last Glacial Maximum (LGM), ∼26, 000 years ago. Moreover, regional sea level varies significantly due to the effects of glacial isostatic adjustment (GIA). That process includes Earth's gravitational, deformational, and rotational response to changing surface (ice plus ocean) loads across the ice age. Here, we offer an updated account of the physics of GIA-induced sea-level change and consider the impacts of these effects, together with a newly published ice sheet history, on sea-level changes across the last glacial cycle. As illustrations, we highlight the significance of these issues for studies of ancient human migration from Sunda to Sahul and for the timing of the final, post-LGM flooding of the Strait of Dover. These examples demonstrate the importance of incorporating updated ice sheet histories and accurate sea-level physics into archaeological research. Highlights: Potential migration pathway models are aided by accurate sea-level reconstructions. "Bathtub" sea level ignores glacial isostatic adjustment spatially variable effects. Updated ice sheet history and accurate sea-level physics shown in case studies. Results have implications for archaeology studies using shoreline reconstructions.